An Investigation of a Conventional Water Treatment Plant in Reducing Dissolved Organic Matter and Trihalomethane Formation Potential from a Tropical River Water Source - Mohamad Rangga Sururi; Suprihanto Notodarmojo; Dwina Roosmini; Prama Setia Putra; Yusuf Eka Maulana; Mila Dirgawati (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
The characteristics and composition of dissolved organic matter (DOM) and trihalomethane (THM) generation during water treatment are important for producing safe drinking water. However, little information is available on this topic within the context of Indonesia. This study aimed to investigate the efficiency of a conventional drinking water treatment plant (WTP) in removing DOM and chloroform forming potential (CHCl3FP), and evaluate surrogate parameters for CHCl3FP. Samples were taken during the rainy season and the dry season from raw water, after secondary treatment and after the rapid sand filter. DOM was characterized based on the A254, A355, SUVA, dissolved organic carbon (DOC), and fluorescence DOM (FDOM) parameters. The composition of the DOM was identified using the peak picking method. Overall, from raw to finished water, the WTP performed better in the rainy season with 55.96% reduction of DOC and 63.45% reduction of A355 as compared to the dry season with 53.27% reduction of DOC and 24.18% reduction of A355.The overall removal of humic and tryptophan compounds during the rainy season was 33.33% and 37.50%, respectively. In the dry season, humic compounds were reduced by 18.80%, while tryptophan increased threefold. A355 can serve as a surrogate parameter for CHCl3FP in raw water and water after secondary treatment, containing more humic-like compounds than tryptophan-like compounds.